Innovations as the Basis for the Implementation of the Smart Port Concept - Adrianna KARAŚ (Communications of International Proceedings, 2022)
The implementation of innovations currently plays an important role in the activities of modern seaports. Innovations conducted in seaports are related to the implementation of modern solutions in line with global trends in international sea shipping. The aim of the article is to review the definition of innovation as an object of divergence in the understanding of this term, as well as the evolution of the concept of innovation. In addition, the Smart Port concept was presented, based on the implementation of innovations and modern technologies by sea ports. The article uses a literature review to generate a representative pool of innovation definitions, and analyzes the content of these definitions to reveal key classifications. The article presents port leaders implementing the Smart Port concept which is integral to the Smart City concept.
Keywords: innovation; seaports; new technologies; Smart Port